2022
DOI: 10.1080/21645515.2021.2008214
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the size of “anti-vax” and vaccine hesitant populations in the US, UK, and Canada: comparative latent class modeling of vaccine attitudes

Abstract: Vaccine hesitancy is a significant impediment to global efforts to vaccinate against the SARS-CoV-2 virus at levels that generate herd immunity. In this article, we show the utility of an inductive approach – latent class analysis (LCA) – that allows us to characterize the size and nature of different vaccine attitude groups; and to compare how these groups differ across countries as well as across demographic subgroups within countries. We perform this analysis using original survey data collected in the US, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Several studies, for example, suggested a link between a study population's race/ ethnicity, sex distribution, and vaccination intention (Allred et al, 2005;Strelitz et al, 2015;Gilkey et al, 2016;Musa et al, 2019;Bell et al, 2020;Kalok et al, 2020;Khattak et al, 2021). These associations could be accounted for by other factors such as family size (Luyten et al, 2019), access to healthcare facilities (Lockyer et al, 2021), healthcare provider discrimination (Woolf et al, 2021), misinformation on social media (Broadbent, 2019), trust in government and/or health authorities (Trent et al, 2022), attitudes towards vaccination (Gravelle et al, 2022), and the fear of vaccine side effects (Karafillakis et al, 2016). As a result, sociodemographic variables such as ethnicity, race, and gender are only carrier variables, not explanatory variables (Schmid et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, for example, suggested a link between a study population's race/ ethnicity, sex distribution, and vaccination intention (Allred et al, 2005;Strelitz et al, 2015;Gilkey et al, 2016;Musa et al, 2019;Bell et al, 2020;Kalok et al, 2020;Khattak et al, 2021). These associations could be accounted for by other factors such as family size (Luyten et al, 2019), access to healthcare facilities (Lockyer et al, 2021), healthcare provider discrimination (Woolf et al, 2021), misinformation on social media (Broadbent, 2019), trust in government and/or health authorities (Trent et al, 2022), attitudes towards vaccination (Gravelle et al, 2022), and the fear of vaccine side effects (Karafillakis et al, 2016). As a result, sociodemographic variables such as ethnicity, race, and gender are only carrier variables, not explanatory variables (Schmid et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a recent bulk of evidence about vaccine hesitancy in the general population and also among kidney transplant patients. Reasons include: concerns about the speed of the COVID-19 vaccine development (in particular, at the beginning of the vaccinal campaign), insufficient vaccine tests, and fear that complications associated with the vaccination could harm the transplant [ 9 ]. Vaccine coverage among kidney transplanted patients could be increased with a clear presentation of the risk–benefit ratio and more information about vaccines and vaccine efficacy in the same risk-population group.…”
Section: Discussionmentioning
confidence: 99%
“…Note that we re-coded the items in a way that higher scores indicate higher vaccine hesitancy. Attitudes towards vaccines more generally correlate highly with citizens’ views of COVID-19 vaccines [18] . We check the robustness of our findings by using feeling thermometer ratings that measure how respondents see COVID-19 vaccines that are approved in the three countries in our sample.…”
Section: Methodsmentioning
confidence: 99%